Rancang Bangun Sistem Informasi Persediaan Barang Pada Afif Jaya Motor Surabaya - Pribadi, Arie Rozzy; Lusiani, Titik; Setyawan, Henry Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: Administrative records of goods in and goods out sloppy and updates resulting in the difference between the existing stock on the record sheet in the warehouse . Parts warehouse difficult to know the most salable items and goods that are not selling well and often there is accumulation of stock even no stock at all for a particular item and place the data redundancy due to the recording of the entry or exit of goods on the record sheet .With these problems it is necessary to Inventory Information System that can perform administrative records of goods in and goods out so there is no difference in stock and redundancy of data items in the warehouse.Given the Inventory Information Systems , part warehouse easier administration and recording of goods in goods out . The system generates reports on expenditures, income statement items , the report returns, inventory taking reports , and report cards needed goods warehouse management to evaluate the activity inventory.